2012
DOI: 10.1103/physreve.85.046310
|View full text |Cite
|
Sign up to set email alerts
|

Particle-accumulation structures in periodic free-surface flows: Inertia versus surface collisions

Abstract: The role of particle inertia and particle-free-surface collisions in periodic free-surface flows is evaluated in the framework of an analytical flow model for a thermocapillary liquid bridge. Inertia and particle-free-surface collisions lead to particle accumulation, but on different time scales, and can lead to different accumulation patterns. A comparison with experimental results provides strong evidence that the experimentally observed accumulation patterns are due to particle-free-surface collisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…,  is the ratio of the particle to the fluid density,  is the so-called relaxation time, related to the tracer radius R by the expression   Unlike earlier studies [17,18], where the particle equation was solved "separately" (the 3D solution was frozen to save computational time and the particle tracking equation solved using such a frozen solution as a "background" state), here eq. (4) has been dynamically integrated together with equation (1-3) (i.e.…”
Section: Mathematical Model and Methods Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…,  is the ratio of the particle to the fluid density,  is the so-called relaxation time, related to the tracer radius R by the expression   Unlike earlier studies [17,18], where the particle equation was solved "separately" (the 3D solution was frozen to save computational time and the particle tracking equation solved using such a frozen solution as a "background" state), here eq. (4) has been dynamically integrated together with equation (1-3) (i.e.…”
Section: Mathematical Model and Methods Of Analysismentioning
confidence: 99%
“…In such a context, it is also worth mentioning Kuhlmann and Muldoon 18 , who addressed the role of "free-surface collisions" in supporting/accelerating the process of transfer of particles from the bulk of liquid to the onedimensional attracting path.…”
Section: Introductionmentioning
confidence: 99%
“…Sapsis & Haller 2010). In particular, the dissipative character of inertial forces changes the structurally unstable trajectories along the closed streamlines into limit cycles which are either attracting or repelling (Kuhlmann & Muldoon 2012). The asymmetry of the evolution of the two particle trajectories in the present system, however, cannot be explained by inertial forces alone, because the flow field and the inertia term in (5.1) are both point symmetric with respect to the cell centre (see also Blohm & Kuhlmann 2002).…”
Section: Inertial Particlesmentioning
confidence: 99%
“…Recently, a number of both experimental Schwabe et al 2006Schwabe et al , 2007Ueno et al 2008;Melnikov et al 2013b) and numerical Pushkin et al 2011;Hofmann and Kuhlmann 2011;Kuhlmann and Hofmann 2011;Kuhlmann and Muldoon 2012;Muldoon and Kuhlmann 2013;Lappa 2013c, b) studies on dynamics of small tracers in a thermocapillary flow in a liquid bridge have been performed aiming at understanding the mechanism of the formation of PAS and finding the best conditions for its existence. It was shown that particles can form a large-scale coherent structure only in a supercritical convective oscillatory flow regime.…”
Section: Introductionmentioning
confidence: 98%